Dampak Sosial Ekonomi Penambangan Pasir dan Batu di Kabupaten Manokwari (Studi Kasus PT Pulau Lemon, Kampung Maruni) - Tika Nadya Indriana Liborang; Ketysia Imelda Tewernusa; Sisilia Maria Parinusa (Fakultas Ekonomi dan Bisnis, Universitas Papua, 2023)
This study aims to determine the impact of sand and stone mining PT. Lemon Island on the socio-economic conditions of the Maruni village community and the economic impact on PT Lemon Island workers. This research uses quantitative research. The social impact is measured by the level of education and welfare, while the economic impact is seen from the income of the community, using an independent sample test, for the social impact there is a difference between the groups receiving and not receiving the impact, while for the economic impact, there is no difference between the groups receiving and received no impact. The economic impact for PT Pulau Lemon's workers is that apart from increasing their income, workers can also fulfill their primary and secondary needs. Penelitian ini bertujuan mengetahui dampak penambangan pasir dan batu PT. Pulau Lemon terhadap kondisi sosial ekonomi masyarakat kampung Maruni dan dampak ekonomi bagi pekerja PT Pulau Lemon. Penelitian ini menggunakan jenis penelitian kuantitatif. Dampak sosial diukur dari tingkat pendidikan dan kesejahteraan , sementara dampak ekonomil dilihat dari pendapatan masyarakat, dengan menggunakan independent sample test, untuk dampak sosial ada perbedaan antara kelompok yang menerima dan tidak menerima dampak, sementara untuk dampak ekonomi, tidak ada perbedaan antara kelompok yang menerima dan tidak menerima dampak. Dampak ekonomi bagi pekerja PT Pulau lemon selain meningkatkan pendapatan, pekerja juga dapat memenuhi kebutuhan primer dan sekunder.